Sedimentologia e estratigrafia quaternária dos depósitos costeiros da região de Vitória, ES - Machado, Giseli Modolo Vieira (2014)
Fluctuations in relative sea level during the Quaternary reveal changes in the architecture and composition of sedimentary deposits due to transgressive / regressive events, energy of the environment and, marine/continental influence. Thus, the stratigraphy has important contribution to the interpretation of these components to predict facies architecture and reconstruct the sedimentation period. Geomorphological evidence is also used to understand the coastal plain evolution. Sedimentological, geochemical and biological indicators are used to recognize the depositional paleoenvironments. The study area comprises the Quaternary coastal deposits of region of Vitória, ES. The area is characterized by a narrow coastal plain between rocks. The methodology is divided into geologic and topographic mapping, stratigraphic, morphoscopic and geochemical analysis. Geologic maps were performed by interpretation of aerial photographs, topographic maps and field trips. The stratigraphic analysis was performed by collecting sediment subsurface through deep cores (SPT) and shallow cores (vibracores). Four deep cores with 20 m drilling on the plain and three shallow cores between 2-5 m drilling on mangroves were performed. Sediments were analyzed by: particle size; organic matter and CaCO3 contents and, shell species classification. Sediments from deep core were also assessed for mineralogical composition and rounding degree, optical appearance and microtextures of quartz grains by optical and scanning electron microscope. Sediments from vibracore were also analyzed for C/N ratio. Twenty datings were performed: 19 by 14C (18 in shells and 1 in organic sediment) e 1 by LOE (quartz). Thus, this thesis aims to investigate the response of coastal sedimentary deposits resulting from fluctuations in sea level during the last 120,000 years in the region. The results contributed to the understanding of the stratigraphic evolution, the role of sea level variations in sedimentary records and the importance of geomorphological control to fill the sedimentation basin. No evidence was found, as sandy terraces associated with the maximum transgression in 120,000 years B.P. The presence of modern estuary, wetlands and beach barrier near the beach current show times of higher sea level during the Holocene. The presence of marine and estuarine shells, fragments of bioclasts, carbonate nodules, C/N ratio below 21 and quartz grains with beach maturity are indicators of marine influence on the environment. Six paleoenvironments were recognized: continental with marine influence, fluvial, bay, estuary, beach barrier and tidal channel. The textural parameters of quartz grains showed little scope of coastal grains within the sedimentation basin. The microtextures by mechanical action on the grain surface indicated predominance of grains related to the fluvial system. Microtextures by chemical action are indicators of environments influenced by marine water and low energy. The proposed evolutionary model for the area is summarized as follows: At isotope stage 5 the region of Victoria was a wide bay with low energy and free connection wit the sea. Around 38,890 ± 180 and > 50,540 years B.P. (isotopic stage 3) the records show a transgressive event in the region. At isotope stage 2, fluvial deposits dominate the plain. The surface of this deposit was dating in 36,307 ± 3292 years B.P. At isotopic stage 1, bay facies dated between 9,448 ± 38 and 7,154 ± 157 cal years B.P., return to occupy the Victoria Bay during transgression, which evolve to estuarine facies to the present. The exposed part a beach barrier is formed around 7,930 ± 150 cal years B.P. and subsequently drowned. Estuary remains with the regression. Some interior areas are transformed into wetlands while, areas near the sea respond to the lowering of sea level by building a beach barrier started at 3,136 ± 185 and 3,201 ± 175 cal years B.P., forming the Camburi plain.